Evaluation of the ANSR® for Salmonella Assay for Identification of Salmonella spp. from Colony Picks from Selective/Differential Agar Media: First Action 2013.14. (27th November 2019) - Mozola, Mark; Botimer, Maximilian; Jagadics, Carolyn; Norton, Paul; Caballero, Oscar; Enslin, Nicole; Biswas, Preetha; Rice, Jennifer; ,
Abstract: A collaborative study was conducted to evaluate performance of the ANSR ® for Salmonella assay for identification of Salmonella spp. from colony picks taken from selective/differential agar media. The ANSR Salmonella assay is an isothermal nucleic acid amplification test based on the nicking enzyme amplification reaction chemistry. The test can be completed in less than 40 min including sample preparation. A total of 18 laboratories representing industry, government, academic, and commercial testing laboratories participated in the study. Each collaborator tested up to 84 samples, comprised of colony picks of six Salmonella spp. and six non-salmonellae taken from six selective/differential agar media as well as tryptic soy agar. A total of 1441 analyses were performed, 1416 of which gave the correct identification, for overall accuracy of 98.3%. For identification of Salmonella spp., 755 of 756 tests (99.9%) produced the correct result. For identification of non-salmonellae as such, 661 of 685 assays (96.5%) produced the correct result. Of the 18 laboratories, 15 produced data sets with 99–100% accuracy. The majority of false-positive results were clustered in three laboratories; analysis of raw data suggests procedural difficulties in at least two cases, which may explain the atypical data from these collaborators. The ANSR Salmonella assay can be used as a rapid, accurate adjunct or alternative to biochemical testing for identification of presumptive Salmonella spp. isolates.